A new species of the pandalid shrimp genus Pandalus (Crustacea: Decapoda: Caridea) from the Sea of Okhotsk off eastern Sakhalin, Russian Far East - Komai, Tomoyuki; Eletskaya, Maria (Zootaxa, 2008)
A new species of the pandalid shrimp genus Pandalus Leach, 1814, Pandalus ivanovi n. sp., is described on the basis of material from the Sea of Okhotsk off eastern Sakhalin, at depths of 150–200 m. It is morphologically closest to Pandalus hypsinotus Brandt, 1851, a commercially important species widely distributed in the northern North Pacific. Because of the strong similarities between the new species and P. hypsinotus, we have examined syntypes of the latter species in order to confirm the specific identity. The new species can be distinguished from P. hypsinotus by the more strongly upturned rostrum, the relatively low postrostral ridge on the carapace, fewer carpal articles of the left second pereopod and the small body size. The coloration in life is also different between the two. There is an indication of protandry in the new species, like other congeneric species.